Tradition and the Past in the Political Thought of the National Party (1928–1939) (Economic and Political Thought, 2019)
The National Party issued generally positive opinions on the nationalpast, invariably stressing the need to establish bonds with the fatherland’shistory and the traditions of the Polish nation. Polish culture was a domainwithin which permanent and imperishable values were observed. The heritageof the past was meant to serve as an impulse to construct the nationstate.The principal objective of this article is to present selected elementsof the National Party’s views on the state’s political system in the contextof political science. Other objectives include outlining the ideological, conceptualand programme-related image of the National Party, along withthe factors determining its ideas, concepts, and views, regarding the state’spolitical system. Analysis of the previous studies on this subject-matter hasrevealed that the scientific reflection on Polish nationalism is still incomplete,and calls for extensive verification. The subject matter dealt with inthis article has filled in a major research gap. Induction was the underlyingresearch method employed by the author. Among the research techniquesused in the study, the analysis of various pieces of evidence and traces ofpolitical thought became the most prevalent. Other research methods whichproved useful in implementing the research objectives included the systematisationof political concepts and a description based on a status-quoanalysis.
Keywords: political thought, National Party, nationalism